2009
DOI: 10.1097/mph.0b013e3181a1c143
|View full text |Cite
|
Sign up to set email alerts
|

Hepatic Iron Overload in Children With Sickle Cell Anemia on Chronic Transfusion Therapy

Abstract: Hepatic iron overload is a serious complication of chronic transfusion therapy in patients with sickle cell disease (SCD). No firm consensus has been reached with regard to correlation between hepatic iron content (HIC) and variables including age, number of transfusions, and serum iron makers. Also, the role of HIC in determining hepatic injury is not well established. There is scarcity of data on chronically transfused children with SCD and no other confounding liver pathology. We aimed to further explore re… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
32
0

Year Published

2009
2009
2016
2016

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 47 publications
(34 citation statements)
references
References 16 publications
2
32
0
Order By: Relevance
“…4). This last finding is similar to that reported by Brown et al, 2009 [10] who showed relationship between hepatic iron content and the transfusion volume in 27 children with sickle cell anemia receiving chronic transfusion therapy [10] .…”
Section: Discussionsupporting
confidence: 92%
“…4). This last finding is similar to that reported by Brown et al, 2009 [10] who showed relationship between hepatic iron content and the transfusion volume in 27 children with sickle cell anemia receiving chronic transfusion therapy [10] .…”
Section: Discussionsupporting
confidence: 92%
“…With ongoing, severe iron loading, non-transferrin-bound iron forms and accumulates in the liver and other organs, such as endocrine glands and the heart, where tissue-damaging free radicals are formed. Untreated, iron overload causes hepatic fibrosis and cirrhosis, diabetes mellitus, hypogonadism, cardiomyopathy, dysrhythmias and sudden death [3][4][5].…”
Section: Introductionmentioning
confidence: 99%
“…Simple transfusion inevitably causes greater positive iron balance than exchange transfusion (Cohen et al, 1992;Kim et al, 1994;Adams et al, 1996;Hilliard et al, 1998;Harmatz et al, 2000;Olivieri, 2001;Brown et al, 2009). Iron accumulation in exchange transfusion depends on the difference between the numbers of red cells removed and those given and is influenced by the type of exchange (manual or automated), as well as Hb and %HbS values pre-and postexchange transfusion (Porter & Garbowski, 2013).…”
Section: Iron Balancementioning
confidence: 99%